2017
DOI: 10.3171/2017.1.peds16568
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a novel simulator for minimally invasive neurosurgery: fusion of 3D printing and special effects

Abstract: OBJECTIVERecent advances in optics and miniaturization have enabled the development of a growing number of minimally invasive procedures, yet innovative training methods for the use of these techniques remain lacking. Conventional teaching models, including cadavers and physical trainers as well as virtual reality platforms, are often expensive and ineffective. Newly developed 3D printing technologies can recreate patient-specific anatomy, but the stiffness of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 49 publications
0
76
0
4
Order By: Relevance
“…Three‐dimensional (3D) printing is a process in which layers of material are successively laid down to generate complex structures, which allows for the creation of relatively inexpensive prototypes . Using imaging data from modalities such as computed tomography (CT) and magnetic resonance imaging (MRI), 3D printing has been used in the medical field to further advancements in prosthetics, undertake perioperative planning of complicated procedures, and facilitate clinical education . Given the complex nature of congenital heart defects (CHD), 3D printing has been increasingly used in this field for anatomic modeling and procedural planning .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐dimensional (3D) printing is a process in which layers of material are successively laid down to generate complex structures, which allows for the creation of relatively inexpensive prototypes . Using imaging data from modalities such as computed tomography (CT) and magnetic resonance imaging (MRI), 3D printing has been used in the medical field to further advancements in prosthetics, undertake perioperative planning of complicated procedures, and facilitate clinical education . Given the complex nature of congenital heart defects (CHD), 3D printing has been increasingly used in this field for anatomic modeling and procedural planning .…”
Section: Introductionmentioning
confidence: 99%
“…1 Using imaging data from modalities such as computed tomography (CT) and magnetic resonance imaging (MRI), 3D printing has been used in the medical field to further advancements in prosthetics, undertake perioperative planning of complicated procedures, and facilitate clinical education. [2][3][4][5][6] Given the complex nature of congenital heart defects (CHD), 3D printing has been increasingly used in this field for anatomic modeling and procedural planning. 7 We have previously reported the utility of 3D printed models in modeling vascular rings and pulmonary slings for resident education.…”
Section: Introductionmentioning
confidence: 99%
“…30 There is emerging evidence in the literature of the superiority of using a 3D visual field in laparoscopic surgery with its improved depth perception. [31][32][33][34][35][36] Therefore, more complex training models with depth and contours could potentially have an impact on the learning curve and enhance A recent study 37 reported a structured training model with a combination of 3D printing and special effects techniques to allow novices to gain valuable experience in surgical techniques without exposing patients to any risk of harm.…”
Section: Discussionmentioning
confidence: 99%
“…Current ETV models have been costly when considering the software required to create the simulator and the need for an operating room-grade endoscope with a light source tower. 2,6,20 Such equipment and resources are not available to the average neurosurgical resident and carry the inherent risk of being damaged with high replacement costs. In this paper we present a method for creating an ETV simulator using free open-source software readily available to the public.…”
Section: Discussionmentioning
confidence: 99%